The Influence of Organizational Communication, Organizational Culture, and Organizational Commitment on Employee Performance - Muhammad Arfan Septiansyah; Editya Nurdiana (Greenation International Journal of Tourism and Management, 2026)
This study, entitled “The Influence of Organizational Communication, Organizational Culture, and Organizational Commitment on Employee Performance,” aims to analyze the extent to which organizational communication, organizational culture, and organizational commitment affect employee performance. The research was conducted on one hundred and ten employees of PT Alido PS using a quantitative approach through a survey method. Data were collected using a questionnaire and analyzed using multiple linear regression to examine both partial and simultaneous effects among the variables. The results indicate that organizational communication and organizational commitment have a positive and significant effect on employee performance, while organizational culture does not show a significant partial effect. However, organizational communication, organizational culture, and organizational commitment collectively demonstrate a significant influence on employee performance. These findings suggest that strengthening internal communication and enhancing employee commitment play essential roles in improving overall employee performance at PT Alido PS.